EZH2 mutations increase the heterogeneity of chromatin states in lymphoma. - Daniel Holoch; Raphaël Margueron (PLoS Biology)
A recent study in PLoS Biology used simultaneous measurements of histone modifications in single cells to reveal that EZH2 gain-of-function mutations profoundly reprogram chromatin states in B-cell lymphoma, while also increasing their cell-cell heterogeneity.